2014
DOI: 10.1603/en13248
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Ratios Document That the Elytra of Western Corn Rootworm (Coleoptera: Chrysomelidae) Reflects Adult Versus Larval Feeding and Later Instar Larvae Prefer Bt Corn to Alternate Hosts

Abstract: In much of the Corn Belt and parts of Europe, the western corn rootworm, Diabrotica virgifera virgifera LeConte, is the most important insect pest of maize. The need for additional basic knowledge of this pest has been highlighted while developing resistance management plans for insecticidal genetically modified crops. This study evaluated the possibility of tracking feeding habits of western corn rootworm larvae using stable carbon isotope signatures. Plants accumulate different ratios of (13)C:(12)C isotopes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Overall, our results suggest that the d 15 N signatures of both soft tissues and elytra of adult P. japonica feeding on 15 N enriched grape leaves change over time, and this change is variable between tissues, with soft tissues showing a higher turnover rate than elytra over time. The d 15 N signatures of both soft tissues and elytra from recently emerged adults that were not fed were not significantly different from each other or from the d 15 N signatures of larvae collected in the same location, which is consistent with previous research showing the isotopic signatures of newly emerged adult beetles can be reliable indicators of larval feeding (Ponsard et al, 2004;Hiltpold et al, 2014;Tsurikov et al, 2015). The elytra of P. japonica had lower d 15 N signatures compared to soft tissues when adults fed on enriched leaves, suggesting that the integument is often isotopically different from other more metabolically active tissues (Tiunov, 2007;Maraun et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our results suggest that the d 15 N signatures of both soft tissues and elytra of adult P. japonica feeding on 15 N enriched grape leaves change over time, and this change is variable between tissues, with soft tissues showing a higher turnover rate than elytra over time. The d 15 N signatures of both soft tissues and elytra from recently emerged adults that were not fed were not significantly different from each other or from the d 15 N signatures of larvae collected in the same location, which is consistent with previous research showing the isotopic signatures of newly emerged adult beetles can be reliable indicators of larval feeding (Ponsard et al, 2004;Hiltpold et al, 2014;Tsurikov et al, 2015). The elytra of P. japonica had lower d 15 N signatures compared to soft tissues when adults fed on enriched leaves, suggesting that the integument is often isotopically different from other more metabolically active tissues (Tiunov, 2007;Maraun et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…A pipette (Eppendorf Research Plus, Hamburg, Germany) was used to deliver the labeled fertilizer directly into each of the holes at the rate of 1 ml of solution per hole. Natural abundances of stable isotopes have provided a field‐tested method to track how generations of a polyphagous pest utilize different host plants (Gould et al., ; Hiltpold et al., ). The 15 N stable isotope of nitrogen provides a reliable, inexpensive, and efficient method of marking WCR (Murphy & Krupke, ).…”
Section: Methodsmentioning
confidence: 99%
“…Although something other than corn was producing WCR beetles in the 1800s, it is noteworthy that corn is currently the only known host plant of WCR in nature 43 . Our previous studies demonstrated that WCR beetles can be produced experimentally on a number of non-corn hosts 13 , 47 49 , though no natural production of WCR has been documented without corn 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Corn roots contain not only feeding stimulants 35 , 36 but also likely provide the best-fit nutrients for corn rootworm development. When roots of both species are present, later instar WCR larvae choose to eat corn roots even those expressing insecticidal toxins (Bt corn) rather than eating one of the better alternate hosts 49 . The differences in the search patterns of the specialist root-feeding larvae, that share intimate coevolution adaptation with these host plants 50 , may reveal that neonates of these species acknowledge their best-fit nutrients.…”
Section: Discussionmentioning
confidence: 99%